Velocity profiling using inertial sensors for freestyle swimming - Stamm, A.; James, D. A.; Thiel, D. V. (Sports Engineering, 2013)
The ability to unobtrusively measure velocity in the aquatic environment is a fundamental challenge for engineers and sports scientists and important in assessing the skill level. The aim of this research was to develop a method for velocity profiling in freestyle swimming utilising a purpose-built inertial sensor. Seventeen swimmers with different experience levels participated in this study performing a total of 159 laps in the velocity range from 0.79 to 2.04 m s-1. Data were collected using a triaxial accelerometer and a tethered velocity meter. The collected acceleration data were filtered using a 0.5 Hz Hamming-windowed FIR filter to remove the gravitational acceleration before the lap velocity profiles were calculated. These calculated lap velocity profiles were then compared with the velocity profiles measured by the velocity meter using Bland-Altman analysis. The scattering follows a normal distribution with a mean skewness of 0.96 ± 0.47 and kurtosis of 2.93 ± 1.12. The results show that an inertial sensor alone can be used to determine a lap velocity profile from single point acceleration records.